Determination of Vitamin C in Various Colours of Bell Pepper (Capsicum annuum L.) by Titration Method - Nerdy Nerdy (ALCHEMY Jurnal Penelitian Kimia, 2018)
Vitamin C is needed by human body to improve the immune system and can be obtained from the bell pepper. Bell pepper has a different color according to the level of maturity, ranging from green, yellow, orange, and red. Differences in color also make possible differences in vitamin C content. The purpose of this study was to determine vitamin C levels in various colors of bell fruit. Measurement of vitamin C was done by titration method with metaphosphoric acid as the solvent and 2,6 dichloroindophenol as the standardized solution. The samples used were green bell pepper, yellow bell pepper, orange bell pepper, and red bell pepper taken from Gundaling, Berastagi, Karo, Sumatera Utara, 22152, Indonesia. The results show that vitamin C level in various colors of bell pepper respectively, for green bell pepper 16.52 mg vitamin C per 100 g green bell pepper; yellow bell pepper 159.61 vitamin C per 100 g yellow bell pepper; orange bell pepper 121.38 vitamin C per 100g orange bell pepper; red bell pepper 81.19 vitamin C per 100 g red bell pepper. These results indicate that different levels of bell pepper maturity have different vitamin C content.